1980
DOI: 10.1111/j.1365-2311.1980.tb01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Kleptoparasitic behaviour of Aphodius rufipes (L.) larvae in nests of Geotrupes spiniger Marsh. (Coleoptera, Scarabaeidae)

Abstract: Abstract. Third instar larvae of A.rufipes were found in short vertical shafts in the soil beneath horse dung and they entered the underground brood masses of G.spiniger when these occurred beneath the same deposit of dung. A.rufipes larvae excavated shafts (60–80mm deep) beneath dung in cages. Just before diapause they burrowed down to the floor of the cage. Burrowing was inhibited in compact soil and in very dry soil. The feeding larvae were attracted to dung and to moisture and they readily attacked oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 4 publications
1
33
0
1
Order By: Relevance
“…It has been proposed that brood parasites could cause death to host larvae directly through larval aggression (Hammond 1976 ;Klemperer 1980) or indirectly via a reduction of food resources for larvae, higher desiccation rates of brood masses, higher vulnerability of the host larvae to fungal infection, or sand grains entering the larval chamber and damaging the teguments of the larvae causing their death (Rougon and Rougon 1980a, 1980b, 1982. Our experiment showed that mortality of O. merdarius larvae was higher in treatments with aphodiid larvae additions (but independent of the number of larvae added), than in the treatment with holes (but without aphodiid larvae), suggesting that the presence of larvae, and not only their indirect effects, was responsible for the death of host larvae.…”
Section: Parasite-host Interaction: Effects On Host Reproductive Successmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been proposed that brood parasites could cause death to host larvae directly through larval aggression (Hammond 1976 ;Klemperer 1980) or indirectly via a reduction of food resources for larvae, higher desiccation rates of brood masses, higher vulnerability of the host larvae to fungal infection, or sand grains entering the larval chamber and damaging the teguments of the larvae causing their death (Rougon and Rougon 1980a, 1980b, 1982. Our experiment showed that mortality of O. merdarius larvae was higher in treatments with aphodiid larvae additions (but independent of the number of larvae added), than in the treatment with holes (but without aphodiid larvae), suggesting that the presence of larvae, and not only their indirect effects, was responsible for the death of host larvae.…”
Section: Parasite-host Interaction: Effects On Host Reproductive Successmentioning
confidence: 99%
“…Larval interaction has been usually ignored except in beetles nesting directly inside the dung pat (Gittings and Giller 1999; but see Holter 1979;Hirschberger and Debro 1996;Hirschberger 1998). This occurs despite the fact that many brood parasitic species alternate different nesting strategies depending on the seasonal climatic conditions (Klemperer 1980;Rougon and Rougon 1980a), and there are even some strict parasitic species (Hammond 1976). Nevertheless, no study has quantified the actual effects that this interaction has on host survival and reproductive success and, therefore, the importance of this interaction as a factor influencing their populations.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…represented 55 % of individuals trapped but are not considered here because most do not bury dung (Kirk, unpublished data), some are not specific dung feeders (Carne, 1950 ;Sears, 1978), and some are kleptoparasitic, e.g. Aphodius porcus (F.) (Chapman, 1869(Chapman, , 1870 and occasionally A. rufipes (L.) (Klemperer, 1980). This study is restricted to species of the Scarabaeinae, and to the Geotrnpini tribe of the Geotrupidae.…”
mentioning
confidence: 98%